Privacy in the YCJA: When Cops and Schools Pass Notes - Abaya, R. Aubrey (Journal of Contemporary Issues in Education, 2025)
In the wake of the killing of George Floyd in 2020, global protests generated public scrutiny about policing in our communities. Between 2020 and 2022, many school boards in Canada began to re-evaluate the value of having police in schools, as school resource officers or school liaison officers, with many boards eventually electing to end these programs altogether. Interactions with police in and through schools can facilitate a process by which youth are pushed out of the school system and into the criminal justice system, commonly known as the school to prison pipeline.The Youth Criminal Justice Act (YCJA), which governs youth in conflict with the law, specifically in their interactions with the justice system and information that is permitted to be shared with other entities like schools. In part, these protections are provided to prevent stigmatization and promote rehabilitation. However, the YCJA had been amended to allow more information disclosures between police and school administrations. This article looks at the legislative history of the YCJA to provide context to these amendments. This article also explores how the court has interpreted privacy for youth under the Act, and how the privacy provisions operate in practice. Finally, it provides empirical research that relies upon interviews with key informants that shed light on the impacts of information sharing between police and schools on youth.